Popular uprisings in the ural district (1929) - Khaidarov, Е. Е. (EDU.E-HISTORY.KZ (электрондық ғылыми журнал), 2022)
In 1929, popular uprisings took place in the Urals region during the grain harvesting campaign. As a result of research, evidence of protests against the policy of collectivization in theZhympitynsky, Zauralny, Kamensky districts was found in the archives of the WKO DP. The article provides a scientific and historical analysis of the causes and consequences, the course ofevents, the social composition of the participants in the anti-Soviet uprisings in Zhympitynsky Zauralny,Kamensky districts of the Ural district. In the course of the study, the protests in the villages of theZhympitinsky district of the Urals district were regarded as the Zhympitinsky uprising. The names of thevictims of political repressions involved in the events in the Zhympitynsky Zauralny, Kamensky districtshave been established, for the first time, on the basis of archival documents, charges and sentences againstthem have been announced. The names of national heroes should be known to the whole country and society, and their strugglefor freedom should be glorified from the standpoint of the state ideology of Independent Kazakhstan. Thepurpose of the commission for the full justification of victims of political persecution is to enable historiansto work with confidential documents, publish the names of innocent politically repressed, justify thempolitically, publish books and collections based on new data.
Keywords: электронный научный журнал; отечественное издание; зко; ринц; история казахстана; народное восстание; Collectivization; grain procurement; popular uprisings; accusations; sentences